Diversidade patogênica em isolados de Thielaviopsis paradoxa provenientes de diferentes áreas produtoras de cana-de-açúcar - Sansoli Chanquinie, Débora Maria [UNESP] (2015)
Thielaviopsis paradoxa, causal agent of pineapple disease is a main cause of poor germination of sugarcane sets. The disease is one of major cause for the reduction of budding and consequent failures on the stand. There is no resistant varieties, and as faster is the plant emergence, less is the damage caused by the pathogen. In this study it was evaluated the pathogenic diversity of eleven isolates of T. paradoxa from stalks of sugarcane with symptoms collected from five Brazilian states (SP, GO, MG, BA and PR). For the inoculation it was used sugarcane sets of the variety IACSP95-5000, with nine months of age. Data analysis revealed differences among the isolates, especially isolates 6 and 7, the most pathogenic, both from Guaíra-SP. The isolated 2, from Santa Juliana-MG was the least pathogenic. Additional tests with three contrasting isolates (low, intermediate and high level of pathogenicity) inoculated in three varieties of sugarcane (IACSP95-5000, IAC911099 and IACSP97-4039) confirmed the different behavior, being reproduced phenotypic characteristics similar to those when inoculated in variety IACSP955000 . The three varieties of sugarcane used in this study showed to be susceptibles, with indication and possible evidence of absence of resistant varieties. It was not found relation between the geographical origin of the isolates and pathogenicity levels. In vitro tests with fungicides of the strobilurin group (pyraclostrobin and trifloxystrobin) and triazole (tebuconazole) at concentrations of 1, 10 and 100μgmL-1 active ingredient, became clear that only the fungicide tebuconazole alone or in combination with trifloxystrobin, showed efficient in inhibiting the size of the colonies, when at 100μgmL-1. Complementary studies about the fungicide viability of the group triazoles, in vitro, at higher ...